Lempar Dawet Tradition: Local Wisdom as an Effort to Ask for Rain in Medang Kamulan, Banjarejo Village - Agung, Rendi Marta; Wulandari, Nuryuana Dwi (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2024)
The Lempar Dawet tradition, a unique rain-inducing ritual practiced in Medang Kamulan hamlet, is deeply rooted in the community's history and cultural values. This qualitative study employed observation, interviews, and documentation, alongside a review of relevant literature, to examine the tradition from multiple perspectives. The Lempar Dawet tradition, originating in the Hindu-Buddhist era, has undergone cultural adaptation with the advent of Islam, while retaining its core essence as a communal response to drought. The study delves into the intricate procedures of the tradition, highlighting the importance of using homemade dawet and the inclusive participation of all community members in the dawet throwing procession. Furthermore, the research uncovers the tradition's inherent character education values, encompassing religiosity, nationalism, independence, mutual cooperation, and integrity, which can be harnessed for educational purposes. This research contributes to a deeper understanding of the Lempar Dawet tradition, its cultural significance, and its potential as a source of character development and environmental adaptation strategies. By shedding light on this unique practice, the study underscores the importance of preserving local wisdom and cultural heritage in an ever-changing world.